Assessment of Pressure Ulcer Risk among Patients in Intensive Care Unit at a Tertiary Care Hospital: A Cross-sectional Descriptive Study - Baral, Pramila; Sapkota, Abja; Gachhadar, Rashmi; Lama, Ishwori; Bhusal, Sita; Thapa, Bikash Raj (Journal of Karnali Academy of Health Sciences, 2020)
Background: Pressure ulcer continues to be a major health problem and prevention has been the main emphasis of patient care. Rigorous evaluation of patients in intensive care unit is necessary for early identification of those at risk of developing pressure ulcer. Multiple risk assessment scales are in practice for its prevention. This study aims to assess pressure ulcer risk of the patients admitted in intensive care unit using Braden Scale. Methods: A cross-sectional descriptive study was conducted among 272 patients admitted in intensive care unit of Nepal Medical College Teaching Hospital from August 2019 to January 2020. Consecutive sampling technique was used to collect data. Data was analyzed using chi-square test and multiple binary logistic regression in the statistical package for social sciences in version 16. Results: Among 272 patients, the mean Braden score of pressure ulcer risk was 18.23±3.51. Nearly half of the patients 127 (46.7%) had risk of developing pressure ulcer, while two of them eventually developed pressure ulcer. The mean age was 51.11±18.82 years. Majority of the patients 221 (81.2%) were admitted in intensive care unit with medical disorders. Risk of developing pressure ulcer was significantly associated with age, gender, fever, use of ventilator, pressure ulcer prevention device, total duration of the hospital stay and duration of Intensive Care Unit stay (p= <0.05). The predictors of pressure ulcer risk were mechanical ventilation (P=0.001, Adjusted Odds Ratio =6.99) and fever (p=0.011, Adjusted Odds Ratio =3.61). Conclusions: Routine use of Braden Scale helps in early identification of pressure ulcer risk. Nurses need to consider the patients with ventilatory support and fever as these are the strong predictors of pressure ulcer risk.